ANALISIS STRUKTURALISME GENETIK DALAM NOVEL MIDAH SIMANIS BERGIGI EMAS KARYA PRAMOEDYA ANANTA TOER - Anggraini, Nani (LPPM STKIP PGRI Bandar Lampung, 2019)
This study discusses how the world view according to the author in Pramoedya Ananta Toer's novel Midah Simanis Bergigi Emas based on genetic structuralism which covers the world view and collective subject and the surrounding environment and how the author views Pramoedya Ananta Toer's Midah Simanis Bergigi Emas novel based on reality history linked to the literary work. The method used in this research is descriptive analytical method. The analysis technique performed is dialectical technique, namely, prioritizing coherent meaning. Dialectic techniques develop two kinds of concepts, namely